PTU-093 Role of MDT in management of benign HPB disease-experience from a non-HPB centre in UK. (8th June 2018) - Firdaus, MS; Elzubier, M; Majumdar, D; Greenaway, J; Craig, DG; Dean, J; Dunn, L; Nkala, L; Hammond, J; French, J; Sen, G; Mitra, V
Abstract : Introduction: In the UK, management of cancer patients are streamlined following discussions in the multi-disciplinary (MDT) meetings. There is growing evidence that MDT meetings play a key role in the management of complex benign diseases. 1 Management of patients with complex pancreatico-biliary diseases can be challenging due to the lack of robust evidence. Further, widespread use of cross-sectional imaging has led to increased detection of incidental pathologies that may or may not be clinically relevant. In view of this, we established a benign HPB MDT in our institution to streamline the management of complex PB patients and report our experience over a period of 12 months. Method: The weekly benign HPB MDT at JCUH is attended by HPB physicians, interventional GI radiologist, specialist nurse, specialist registrars, upper GI surgeon and the visiting surgeon from the regional tertiary HPB unit. Referrals are sent via a dedicated pro-forma and recommendations are recorded electronically on the trust's info-flex software system. Retrospective analysis of a prospective maintained database was carried out between January 2017 to December 2017. Data was collected on patient demographics, cross-sectional imaging, diagnosis and clinical outcomes. Results: 263 patients were discussed (55% males) for benign indications. Median age was 67 years (range 21–91 years). The main reasons for MDT referral are summarised below: Incidental pancreatic cysts 76 (29%) Pancreatitis (acute/chronic/recurrent) 61 (23%) Complex CBD stones 33 (13%) Indeterminate biliary stricture 17 (6%) Complex GB pathology 16 (6%) Unexplained biliary and pancreatic duct dilation on imaging 11 (4%) Autoimmune pancreatitis 3 (1%) Others [e.g. bile leak, choledochal cyst, duodenal polyp, liver cyst, sphincter of Oddi dysfunction etc] 46 (18%) The MDT's recommendations were the following; Medical pancreatic clinic follow up: 53 Radiological surveillance: 86 Surgical clinic follow up: 53 Endoscopic interventions: 49 Radiological intervention: 8 Referral to regional tertiary HPB surgical clinic: 43 Discharge back to GP: 22 Conclusion: Our data shows that the Benign HPB MDT facilitated the management of this complex group of HPB patients locally by the appropriate teams and fast tracked further management of selected complex patients at the regional centre requiring surgery and specialised endoscopic intervention. Reference: . Noor LH, Bekkali, et al. The role of multidisciplinary meetings for benign pancreatobiliary diseases: a tertiary centre experience. Frontline GastroenterologyJuly 2017;8(3).